Impact of "El Niño 1997-98" on shallow marine ecosystem of the Peruvian central coast - Tarazona B., Juan (1999)
The characteristics of intensity, and untimely of "El Niño 1997-98" answer, manifested by superficial phytoplankton, rocky shore macroalgae, and soft bottom macrobenthos were analyzed from December 1996 to August 1998 in Ancon Bay (11 °46' LS and 77°11' LW). A significative increase of both, temperature since April (17,4°C), and oxygen (2,46 mLL-1)from May 1997 in the bottom of the study area, characterized this event. In superficial phytoplankton, the presence of indicator species of warm oceanic water, and an unusual increase of both dinoflagellate and microflagellate density at the beginning of April 1997 were recorded since January. The density of Chondracanthus chamissoi population reached 2684 ind.x32 m ' of shoreline in October 1997, and the proportion 01 gametophytes increased during 1998. The density and species number 01 soft bottom macrobenthos reached maximum values of 90 indo x 0,04 m-2, and 20 species in June, and November 1997 respectively; these variations have a good correlation with intensity changes of "El Niño". The biomass reached its maximum value 0,55 g pssc x 0,04 m-2 in January 1998. Finally, it is showed that "El Niño 1997-98" biological impact was lesser than that of 1982-83 however the similarity of intensity in both events; and that shallow water showed early and reliable indicators of "El Niño", in both, the phytoplankton as in the benthos. Moreover, the presence of a post-Niño period showed that "El Niño" impact on population and communities might be complex.